Theoretical study of the solvent effects on the molecular structure and vibrational spectra of 2-hydroxy-4-methyl-3-nitropyridine - Polat, Turgay (Elsevier BV, 2014)
Abstract Solvent effects on 2-hydroxy-4-methyl-3-nitropyridine molecule in different solvents (benzene, toluene, chloroform, acetone and water) were studied theoretically at the DFT/B3LYP level in combination with the conductor polarizable continuum model (CPCM) for the first time. Based on these results vibrational spectra were simulated. The role of the solvent polarity on the molecule stability, the optimized geometry, atomic charges (for charge distribution), dipole moments (for molecular charge transfer) and vibrational spectra belonging to title molecule was discussed in detail. It was found that the O H and NO2 stretching vibrations shift regularly to lower frequency value with higher IR intensity and the C H stretching vibrations shift to higher frequency value. The results obtained indicate not only the presence of the hydrogen bonding and strong intra-molecular charge transfer in the compound but the molecule stability with the solvent polarity, as well. Additionally, the complexes of title molecule−water were simulated to describe the effect of intermolecular hydrogen bonding on the molecular geometry and vibrational frequencies. It was found that the O H stretching vibrations shift regularly to lower frequency value with higher IR intensity due to the intermolecular H⋯O hydrogen bonds.
Keywords: 3. Good health